Spatial and economic effects of TOKI practices in the context of public housing investments: The Erzincan example - Banu Tantan; Sevkiye Sence Turk (Journal of Design for Resilience in Architecture and Planning, 2026)
Housing Development Administration of the Republic of Türkiye (TOKI), which was established as a public legal entity in 1984 to provide solutions to urbanization and housing problems, became the most important actor in steering urbanization and housing policies with the powers granted to it after 2002. This study analyzes public housing production in Türkiye through TOKI’s housing policies, with a particular focus on the transformation of housing policy that has occurred since 2002. The aim of the study is to examine the economic and spatial impact of public housing investments at the local level, focusing on the Erzincan city center as an exploratory case study, where TOKI has invested the most, and as an example of non-metropolitan provinces. The study attempts to measure the impact of TOKI investments at the local level, both economically and spatially, through a total of seven variables using the descriptive analysis method and the spatial analysis method. The analysis revealed that TOKI manifested exclusively as an earthquake, disaster, or social housing practice, devoid of any discernible direct economic impact. It has been observed that the practices of TOKI exerted a multifaceted influence on the urban spatial development, exhibiting both positive and negative spatial implications.